1986
DOI: 10.1152/jappl.1986.61.4.1499
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of postinspiratory activity of phrenic motoneurons with chemical and vagal reflexes

Abstract: We examined the effects of chemical and reflex drives on the postinspiratory inspiratory activity (PIIA) of phrenic motoneurons using a single-fiber technique. Action potentials from "single" fibers were recorded from the C5 phrenic root together with contralateral mass phrenic activity (also from C5) in anesthetized, paralyzed, and artificially ventilated cats with intact vagus and carotid sinus nerves. Nerve fibers were classified as "early" or "late" based on their onset of discharge in relation to mass phr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Early-I PMNs show more action potential spikes per breath, and have a longer overall discharge duration compared to Late-I cells. However, the mean discharge frequency and the interspike interval are similar between Early-I and Late-I PMNs (Hilaire et al, 1983; Hwang and St John, 1993; Kong and Berger, 1986; Lee et al, 1990; Lee et al, 2009; Prabhakar et al, 1986; St John and Bartlett, 1979, 1981). A few studies have reported that Early-I, but not Late-I PMNs can continue bursting during the post-inspiratory period (Kong and Berger, 1986; Prabhakar et al, 1986).…”
Section: Pmn Discharge Patternsmentioning
confidence: 90%
See 2 more Smart Citations
“…Early-I PMNs show more action potential spikes per breath, and have a longer overall discharge duration compared to Late-I cells. However, the mean discharge frequency and the interspike interval are similar between Early-I and Late-I PMNs (Hilaire et al, 1983; Hwang and St John, 1993; Kong and Berger, 1986; Lee et al, 1990; Lee et al, 2009; Prabhakar et al, 1986; St John and Bartlett, 1979, 1981). A few studies have reported that Early-I, but not Late-I PMNs can continue bursting during the post-inspiratory period (Kong and Berger, 1986; Prabhakar et al, 1986).…”
Section: Pmn Discharge Patternsmentioning
confidence: 90%
“…Hypoxia, as expected, increases the discharge frequency of both Early-I and Late-I PMNs and recruit previously silent cells. Late-I PMNs also show an earlier burst onset during hypoxic stimulation (Lee et al, 1990; Lee et al, 2009; Prabhakar et al, 1986; St John and Bartlett, 1979). We recently observed that hypoxia induces differential responses in Early-I vs. Late-I PMNs (Lee et al, 2009).…”
Section: Pmn Discharge Patternsmentioning
confidence: 96%
See 1 more Smart Citation
“…Next, force generated at 40 H Z by direct muscle stimulation (P 40 M) was measured, to obtain a measure of the quality of the preparations. A stimulation frequency of 40 H Z was chosen because diaphragm motor units typically fire at frequencies ranging from 20 to 40 H Z when breathing is stimulated by hypoxia 35, 44. Subsequently, the perfusion of the tissue bath was either maintained at hyperoxia (95%O 2 –5%CO 2 ) or switched to hypoxia (95%N 2 –5%CO 2 ); the Krebs solution was replaced by the experimental Krebs solutions.…”
Section: Methodsmentioning
confidence: 99%
“…hypercapnia and hypoxia) specifically induced an earlier discharge in Late‐I but not Early‐I phrenic motoneurons (Kong & Berger, ; Prabhakar et al . ; Lee et al . ).…”
Section: Introductionmentioning
confidence: 99%